Structural and kinetic characterization of DUSP5 with a Di-phosphorylated tripeptide substrate from the ERK activation loop - Imhoff, Andrea; Sweeney, Noreena L.; Bongard, Robert D.; Syrlybaeva, Raulia; Gupta, Ankan; Del Carpio, Edgar; Talipov, Marat R.; Garcia-Keller, Costanza; Crans, Debbie C.; Ramchandran, Ramani; Sem, Daniel S. (Frontiers in Chemical Biology, 2024)
Dual specific phosphatases (DUSPs) are mitogen-activated protein kinase (MAPK) regulators, which also serve as drug targets for treating various vascular diseases. Previously, we have presented mechanistic characterizations of DUSP5 and its interaction with pERK, proposing a dual active site. Herein, we characterize the interactions between the DUSP5 phosphatase domain and the pT-E-pY activation loop of ERK2, with specific active site assignments. We also report the full NMR chemical shift assignments of DUSP5 that now enable chemical shift perturbation and dynamics studies. Both phosphates of the pT-E-pY tripeptide are dephosphorylated, based on 31 P NMR; but, steady state kinetic studies of the tripeptide both as a substrate and as an inhibitor indicate a preference for binding and dephosphorylation of the phospho-tyrosine before the phospho-threonine. Catalytic efficiency (kcat/Km) is 3.7 M -1 S -1 for T-E-pY vs.1.3 M -1 S -1 for pT-E-Y, although the diphosphorylated peptide (pT-E-pY) is a better substrate than both, with kcat/Km = 18.2 M -1 S -1 . Steady state inhibition studies with the pNPP substrate yields Kis values for the peptide substrates of: 15.8 mM (pT-E-Y), 4.93 mM (T-E-pY), 1.67 mM (pT-E-pY). Steady state inhibition studies with pNPP substrate and with vanadate or phosphate inhibitors indicated competitive inhibition with Kis values of 0.000612 mM (sodium vanadate) and 17.3 mM (sodium phosphate), similar to other Protein Tyrosine Phosphatases with an active site cysteine nucleophile that go through a fivecoordinate high energy transition state or intermediate. Molecular dynamics (MD) studies confirm preferential binding of the diphosphorylated peptide, but with preference for binding the pY over the pT reside in the catalytic site proximal to the Cys263 nucleophile. Based on MD, the monophosphorylated peptide binds tighter if phosphorylated on the Tyr vs. the Thr. And, if the starting pose of the docked diphosphorylated peptide has pT in the catalytic site, it will adjust to have the pY in the catalytic site, suggesting a dynamic shifting of the peptide orientation. 2D 1 H-15 N HSQC chemical shift perturbation studies confirm that DUSP5 with tripeptide bound is in a dynamic state, with extensive exchange broadening observedespecially of catalytic site residues.